2000
DOI: 10.4049/jimmunol.165.2.786
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of CD153 (CD30 Ligand) by CD30+ T Cells Inhibits Class Switch DNA Recombination and Antibody Production in Human IgD+ IgM+ B Cells

Abstract: CD153 (CD30 ligand) is a member of the TNF ligand/cytokine family expressed on the surface of human B cells. Upon exposure to IL-4, a critical Ig class switch-inducing cytokine, Ag-activated T cells express CD30, the CD153 receptor. The observation that dysregulated IgG, IgA, and/or IgE production is often associated with up-regulation of T cell CD30 prompted us to test the hypothesis that engagement of B cell CD153 by T cell CD30 modulates Ig class switching. In this study, we show that IgD+ IgM+ B cells up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 73 publications
(71 reference statements)
0
78
0
Order By: Relevance
“…on April 2, 2019. by guest www.bloodjournal.org From Thus, engagement of CD30 by CD153, which is associated preferentially with Th2-type effector responses, 19 regulates CXCR4 and CCR7 27 expression and delivers inhibitory signals, 20,27 leading to impaired clonal expansion of peripheral T cells, 21 sensitizing to TNFR1-dependent apoptosis, 3 and counteracting IgG and IgA production. 52 This cellularlevel regulation seems to have a counterpart in a number of conditions, sharing the tendency to selective compartmentalization of lowproliferating CD30 ϩ cells, which deliver locally anti-inflammatory cytokines, such as IL-4 and IL-10, whenever tested for 16 and which generate a molecular milieu characterized by features of immune suppression. 16,20 These conditions include autoimmune diabetes in mouse models, 21 rheumatoid arthritis, 16 Omenn syndrome, 14 a severe immunodeficiency characterized by features reminiscent of a Th2-type response in which large proportions of tissue-infiltrating CD30 ϩ cells are present, measles 53 in which CD30 ϩ cell expansion is related to the impaired mitogenic capability of T lymphocytes, inadequate Th1-type responses, and cell recruitment to lymph nodes and skin.…”
Section: Discussionmentioning
confidence: 99%
“…on April 2, 2019. by guest www.bloodjournal.org From Thus, engagement of CD30 by CD153, which is associated preferentially with Th2-type effector responses, 19 regulates CXCR4 and CCR7 27 expression and delivers inhibitory signals, 20,27 leading to impaired clonal expansion of peripheral T cells, 21 sensitizing to TNFR1-dependent apoptosis, 3 and counteracting IgG and IgA production. 52 This cellularlevel regulation seems to have a counterpart in a number of conditions, sharing the tendency to selective compartmentalization of lowproliferating CD30 ϩ cells, which deliver locally anti-inflammatory cytokines, such as IL-4 and IL-10, whenever tested for 16 and which generate a molecular milieu characterized by features of immune suppression. 16,20 These conditions include autoimmune diabetes in mouse models, 21 rheumatoid arthritis, 16 Omenn syndrome, 14 a severe immunodeficiency characterized by features reminiscent of a Th2-type response in which large proportions of tissue-infiltrating CD30 ϩ cells are present, measles 53 in which CD30 ϩ cell expansion is related to the impaired mitogenic capability of T lymphocytes, inadequate Th1-type responses, and cell recruitment to lymph nodes and skin.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed physiologic functions of CD30L include a role in T-cell costimulation, cytokine and chemokine secretion, regulation of class-switch DNA recombination, and antibody production in subsets of human B cells. 23,24 CD30L has diverse biologic activity in different CD30ϩ cancers, ranging from enhancement of survival to no induction of apoptosis and cell cycle arrest. 14,[25][26][27][28][29] These paradoxical effects are caused by a differential effect on NF-B activation.…”
Section: Cd30 Receptor and Cd30l (Cd153)mentioning
confidence: 99%
“…Cayabyab et al 10 and Van Essen et al 11 have shown that CD40L transduces costimulation signals into T cells. Wiley et al 12 have reported that CD30L cross-linking activates neutrophils, and Cerutti et al 13 showed that such reverse signaling inhibits the immunoglobin class switch in B cells. Reverse signaling through membrane TNF-␣ confers resistance of monocytes and macrophages to lipopolysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…3,20 Mouse TR6 has not been cloned. Human TR6 has 3 known ligands, FasL, 13 LIGHT, 3,4 and TL1A. 21 FasL binding by TR6 interferes with the interaction between Fas and FasL.…”
Section: Introductionmentioning
confidence: 99%